Response of maize to N and P in two trials in Uganda - Sommer, Rolf; Kihara, Job Maguta; Kinyua, Michael (International Center for Tropical Agriculture, 2019)
These data were produced with co-funding provided by the AgMIP project, and funds received via CGIAR CRP WLE (2013)